Speech text of virtual signing ceremony: memorandum of understanding between Universiti Teknologi MARA and Vels Institute of Science Technology and Advanced Studies (VISTAS) / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
It is indeed an honour for me to be here at the virtual Memorandum of Understanding (MoU) signing ceremony between Universiti Teknologi MARA (UiTM) and the Vels Institute of Science Technology and Advanced Studies or better known as VISTAS.Today marks an important milestone for UiTM and VISTAS. It is also a testament to the continued effort made by both academic institutions to forge global partnerships in hopes of achieving academic visibility and excellence.